Modelling of Heat Transfers, Phase Changes and Mechanical Behaviour during Welding - Fortunier, Roland; Bergheau, Jean-Michel (European Journal of Computational Mechanics, 2004)
This paper describes the main models used in finite element software for welding simulations. Welding involves thermal transfers from the weld zone to the rest of the structure and thus leads to loadings due to thermal gradients and tools. Moreover, the temperature reaches locally relatively high values, so that the evolution of the microstructure in the material has to be taken into account. The main physical mechanisms involved during welding imply fully coupled thermal transfers and phase changes models, and thermomechanical models involving transformation induced plasticity. These models are described, and the concluding remarks outline particular points that are to be more investigated in the future.